Sharia Economic Views on Tabzir Behavior - Sukoco, Daud; Retnowati, May Shinta; Rofiqa, Azidni; Firdaus, Muhammad Irkham; Sup, Devid Frastiawan Amir (AL-IKTISAB: Journal of Islamic Economic Law, 2021)
Tabzir behavior is a form of deviation in economic behavior, especially consumption. The purpose of this study is to describe the concept of tabzir in Islamic economic studies and to provide an ideal behavioral offer for consumer behavior. The research method used is qualitative-descriptive-library. Data were collected by documentation method, then processed by data editing and compilation method. Next, the analysis process was carried out by deduction method using the concept of tabzir in Islamic economic studies. Conclusions drawn from this study. First, tabzir behavior is a form of malpractice and deviation in economic behavior, especially in consumption. Second, the law of tabzir behavior for certain definitions is haram. Third, the wisdom avoid of tabzir behavior is to build an awareness of collective solidarity, avoid debt, disorientation of life loss of critical power and economic education. The social concept about consumption based on sharia is a social care which concern on tauhid and love for fellow human beings, thus forming a just and civilized society.